Державне регулювання в системі фізичного виховання у закладах вищої освіти України. - Малинський, Ігор Йосипович; Malynskyi, Ihor Yosypovych (Ірпінь, 2023)
Обґрунтування науково-методологічних підходів та розробка практичних рекомендацій для органів державної влади з уніфікації механізмів державного регулювання системі фізичного виховання у закладах вищої освіти у закладах вищої освіти України на сучасному етапі

Substantiation of scientific and methodological approaches and development of practical recommendations for public authorities on unification of mechanisms of state regulation of the system of physical education in higher education institutions in higher education institutions of Ukraine at the present stage
State regulation in the system of financial protection in the foundations of the higher education of Ukraine.
Keywords: державне регулювання; ефективність; система; фізична культура; спорт; заклади вищої освіти; state regulation; system; effectiveness; physical culture; sports; higher education institutions